EXPORT-IMPORT RELATIONS OF SOVIET CINEMA DURING THE YEARS OF «STAGNATION» - M. Kosinova (Вестник университета)
The article discusses issues related to international hire of domestic cinema in the period of Stagnation, as well as procurement policy in the field of cinema. These issues were dealt with such organization as «Sovexportfilm». This period is characterized by a number of difficulties in the field of export-import relationship, caused by the reasons of objective nature (for example the «Сold war» between the USSR and the USA), and the subjective relevance to the problems within the Soviet film industry (the decline of the artistic and technical level will domestic movie).